Cannibals with forks the triple bottom line of 21st century business - Elkington, John. (Gabriola Island New Society Publishers, 1999)
Cannibals with Forks passionately demonstrates how all businesses can and must help society achieve the three inter?linked goals of economic prosperity,environmental protection and social equity, issues which are already at the top of the corporate agenda.
Includes bibliographical references and index.
Keywords: Industrial management -Environmental aspects